ANALYSIS OF COMMUNITY PARTICIPATION IN THE FREE CORONA VIRUS DISEASE 2019 (COVID -19) VACCINATION PROGRAM AT THE LISU HEALTH CENTER, KADING VILLAGE, TANETE RIAJA DISTRICT, BARRU REGENCY - Nurlia Nurlia; Hasmawati Hasmawati (Jurnal Scientia, 2023)
This study aims to determine community participation and the factors that influence community participation in the free corona virus disease 2019 (covid -19) vaccination program at the Lisu Health Center, Kading Village, Tanete Riaja District, Barru Regency by using a qualitative descriptive research type, the type of data used consists of primary data, and secondary data accompanied by the collection techniques applied, namely observation, interviews, and documentation. While the data analysis techniques through the stages of data collection, data reduction, data presentation and drawing conclusions.The results of this study indicate that public participation in the free corona virus disease 2019 (covid-19) vaccination program at the Lisu Health Center, Kading Village, Tanete Riaja District, Barru Regency is still low, including participation in decision making, implementation of activities and their benefits, while the factors that influence namely the fear of the side effects of the covid-19 vaccination and the many events on social media that he might see including hoax news so that people do not participate in covid-19 vaccination activities.